O desenho geométrico no ensino da geometria: uma sequência didática - Silva, Willamy Adriano Matias da (2019)
The data from the large-scale assessments show us that school education in Brazil is in crisis and, amid this crisis, one of the weaknesses is in mathematics teaching and learning process. This paper presents a bibliographic research, in which we present the history of mathematics teaching, focusing on geometry, and the history of geometric design and its influence on other branches of science and arts. This research reflects the modus operandi of the researcher, who teaches geometry classes with the support of the ruler and compass in basic education. This paper aims to show an alternative to improve students' learning in this area of mathematics, which has been neglected in recent decades, with a strong influence of the Modern Mathematics Movement, which sought to focus teaching on algebraic procedures to the detriment of geometrical ones. This paper aims to show an alternative to improve students' learning in this area of mathematics, which has been neglected in recent decades, with a strong influence of the Modern Mathematics Movement, which sought to focus teaching on algebraic procedures to the detriment of geometrical ones.